Recommendations for Reducing Progressive Collapse Potential in Flat Slab Structural Systems. Issue 5 (February 2019) - Mohamed, Osama; Khattab, Rania Al; Mishra, Anamika; Isam, Feda
Abstract: Flat slab structural systems are amongst the oldest methods to transfer gravity loads and contribute to resistance of lateral forces. The popularity of the system is owed to the ease and speed of construction compared to other floor systems. Flat slabs also offer flexibility where light and heavy partitions may be placed freely anywhere on plan. Properly designed flat slabs possess considerable ability to transfer vertical loads through membrane action. However, in the event of loss of primarily load-carrying system, the potential for progressive collapse is relatively high. This is due to the inherent lack of alternate load path to transfer gravity load and mitigate progressive collapse. Compared to interior columns, Loss of corner and exterior columns produces higher local demands on the slab and increases the potential for global progressive collapse in the panels at the vicinity of lost corner columns. This paper discusses the dominant failure modes associated with progressive collapse in flat slab construction. The paper also explores options for geometric and structural design of flat slab system that will enhance resistance for progressive collapse with better life safety. The following measures for reducing progressive collapse potential are discussed: 1) use of enhanced local resistance approach for corner and penultimate columns, 2) use of edge beams along perimeters to increase stiffness and improve load transfer, 3) detailing requirements for flat slab system to decrease the potential for punching shear and where continuity and anchorage of bottom reinforcement through columns was noted as critical in improving collapse resistance; 4) selecting columns configurations with improved resistance to punching shear and buckling, 5) addressing the inherently lower collapse resistance in corner slab panels through judicial selection of shear wall locations incorporated with perimeter exterior beams to form a load path.